Electric vehicles acceptance capacity evaluation in distribution network considering photovoltaics access. (March 2023) - Ji, Yang; Zhang, Jian; Li, Siwei; Deng, Youjun; Mu, Yunfei
Abstract: In the power system with a high proportion of new energy access, the original electric vehicle charging operation mode of the distribution network will change, and the acceptance capacity of electric vehicles also needs to be re-evaluated. In this paper, an evaluation method for the acceptance capacity of electric vehicles is proposed for the distribution network with photovoltaic power generation system installed. Considering the random variation characteristics of the output of the photovoltaic power generation system, seasonal periodicity, and the influence of weather factors, an evaluation model is established. It uses the particle swarm optimization algorithm to calculate the number of electric vehicles that the photovoltaic power generation system can accept, and to analyze the acceptance capacity of the distribution network for electric vehicles. The method utilizes the photovoltaic output to fill the electric vehicle charging demand, and can realize the mutual consumption of the electric vehicle charging and the photovoltaic output.